Application of the Garcia-Wachs Algorithm to Build a Minimum Cost Search Tree - Gadasin, D. V.; Palibza, S. A.; Tremasova, L. A.; Zimnin, A. S. (Systems of Signals Generating and Processing in the Field of on Board Communications (Online), 2025)
The attribute values of a certain subject area can be ordered according to the probability of their occurrence, and based on them it is possible to build a tree on which to implement a search algorithm and determine whether the search data is valid for the selected attribute. One of the possible structures of the domain representation is a tree, and the search for the necessary attribute can take place on the search tree. In a binary search tree, any internal vertex is connected by two links, either with internal vertices, or with external vertices, or with internal and external ones. The key characteristic of the tree is the cost of the tree, which corresponds to the average length of the path from the root vertex to the outer one. One of the algorithms for building a minimum cost search tree is the Garcia-Wachs algorithm. This algorithm builds an optimal binary tree based on a predefined order. The paper considers various initial states and determines the most suitable ones.